2002
DOI: 10.1007/bf02705048
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic studies of the corpuscles of Stannius of an airbreathing teleost (Heteropneustes Fossilis)

Abstract: The ultrastructure of the corpuscles of Stannius (CS) of Heteropneustes fossilis reveals a homogenous cellular composition characterized by only one cell type, with large secretory granules and abundant ribosomal endoplasmic reticulum. These cells are comparable to the type 1 cell described in the CS of other teleosts; type 2 cells, whose presence is ubiquitous in the CS of freshwater species are absent in H. fossilis. Our data on the CS of H. fossilis demonstrate that not all freshwater species possess type 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In order to collect more information on the cellular composition of Stc, we have investigated the histological and ultrastructure of the Stc in two teleostean fish, fresh water O. niloticus and marine fish E. tuvina. Ahmad et al (2002) in their study on Heteropneustes fossils revealed only one cell type with large secretory granules and abundant rough endoplasmic reticulum.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In order to collect more information on the cellular composition of Stc, we have investigated the histological and ultrastructure of the Stc in two teleostean fish, fresh water O. niloticus and marine fish E. tuvina. Ahmad et al (2002) in their study on Heteropneustes fossils revealed only one cell type with large secretory granules and abundant rough endoplasmic reticulum.…”
Section: Introductionmentioning
confidence: 96%
“…Recently, stanniocalcin has been localized in different mammalian tissues including human tissues (Chang & Reddel, 1998;Luo et al, 2004 andSong et al, 2006). The human stanniocalcin revealed homology in the chemical structure to fish stanniocalcin and the data imply that this hormone regulates the female reproductive system (Mc-Cudden et al, 2001;Ahmad et al, 2002;Varghese et al, 2002;Luo et al, 2005 andSong et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The number and anatomical localization of the Sc in the kidneys may vary among the fish species (Bedjargi & Kulkarni, 2014a; Krishnamurthy & Bern, 1969). Although previous ultrastructural and histological studies reported two different cell types constituting the gland in general (Abu Zinadah et al., 2006; Bhattacharyya & Butler, 1978; Chakrabarti & Banerjee, 2016; Krishnamurthy & Bern, 1969; Wendelaar Bonga & Greven, 1975; Wendelaar Bonga et al., 1977; Wendelaar Bonga et al., 1980), only a single type or a third type of cell has been reported in the glands of some fish species (Ahmad et al., 2002; Bedjargi & Kulkarni, 2014a, 2014b; Pinheiro et al., 1987). The staining pattern of the cell types in the gland using histological stains, such as periodic acid‐Schiff (PAS) and aldehyde fuchsin (AF) may also differentiate between fish species (Krishnamurthy & Bern, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…Despite extensive research on fish CS [ 17 24 ], the debate concerning its cellular population is still open. Two structurally different cell types have been reported in the CS of several teleosts [ 17 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two structurally different cell types have been reported in the CS of several teleosts [ 17 21 ]. On the other hand, researchers also have noticed only one cell type in the CS of some other teleosts [ 22 – 24 ]. It is still unclear whether these represent different physiological conditions of a single cell type or depict functionally different cell types.…”
Section: Resultsmentioning
confidence: 99%